Construction and Expression of the Chimeric Human Renalase Gene Encoding the N-Terminal Signal Sequence of the Secretory Protein Prolactin - Fedchenko, V.I.; Kaloshin, A.A.; Veselovsky, A.V.; Medvedev, A.E. (Biomedical Chemistry: Research and Methods, 2022)
Renalase (RNLS) is a protein that performs various protective functions both inside and outside cells. Intracellular RNLS is a FAD-dependent oxidoreductase (EC 1.6.3.5). Extracellular RNLS lacking an N-terminal peptide does not interact with FAD and exhibits various protective effects on the cell through interaction with receptor proteins. The mechanisms and factors responsible for RNLS transport out of the cell are not fully understood. It is well known that the signal sequence plays a key role in the classical mechanism of protein transport outside cells. One of the approaches to study the secretion of RNLS from the cell can be the creation of chimeric forms of the protein with a modified N-terminal amino acid signal sequence. Bioinformatics analysis showed that the signal sequence of the prolactin gene (PRL), connected to the template sequence of the RNLS gene, gave the classic signal characteristic of secretory proteins. On this basis, this paper describes: (i) a method for constructing the human RNLS gene in which the N-terminal sequence encoded by the RNLS gene was replaced by the N-terminal sequence encoded by the PRL gene; (ii) expression of this chimeric genetic construct.